2020
DOI: 10.24198/jkg.v32i2.27117
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pengaruh edukasi kesehatan gigi dan mulut berbasis buku Braille terhadap tingkat kebersihan gigi dan mulut penyandang tunanetra di SLB-A TPA dan SLB Negeri Jember</p><p>The effect of oral health education in the form of Braille book towards the oral hygiene status of visually impaired student attending Special School-A TPA and Public Special School of Jember</p>

Abstract: Pendahuluan: Tunanetra merupakan istilah yang digunakan untuk kondisi seseorang yang mengalami gangguan dalam indera penglihatannya. Keterbatasan fisik yang dialami oleh tunanetra menyebabkan pengetahuan tentang kesehatan gigi dan mulut sulit didapatkan dan cenderung memiliki tingkat kebersihan gigi dan mulut yang rendah. Oleh karena itu diperlukan pendekatan khusus agar pengetahuan dan kebersihan gigi dan mulut dapat meningkat. Tujuan penelitian ini untuk menganalisis pengaruh edukasi kesehatan gigi dan mulut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…[24] Research by Istadi (2020) on blind children who were given tooth brushing training with braille book, after 21 days of training, he found that there was a decrease in OHI-S index which was statistically proven (p<0.05). 27 Another study conducted on children with intellectual disabilities also found that tooth brushing training significantly reduce the plaque index score (p<0.05). 20 Tooth brushing training is a good way to empower children in oral hygiene activities independently, especially for SNC.…”
Section: Discussionmentioning
confidence: 93%
“…[24] Research by Istadi (2020) on blind children who were given tooth brushing training with braille book, after 21 days of training, he found that there was a decrease in OHI-S index which was statistically proven (p<0.05). 27 Another study conducted on children with intellectual disabilities also found that tooth brushing training significantly reduce the plaque index score (p<0.05). 20 Tooth brushing training is a good way to empower children in oral hygiene activities independently, especially for SNC.…”
Section: Discussionmentioning
confidence: 93%
“…Tingkat kebersihan gigi dan mulut anak tunanetra usia 12-15 tahun umumnya tergolong dalam kategori buruk. 2 Terjadi peningkatan masalah kesehatan gigi dan mulut, salah satunya pada kesehatan gingiva sebesar 25,9%; lebih dari 80% penderita ialah anak usia muda. 3 Upaya untuk meningkatkan kebersihan gigi dan mulut anak tunanetra dapat dilakukan dengan meningkatkan pengetahuan serta pendampingan saat menjaga kebersihan dan mulut yaitu dengan mengajarkan cara menyikat gigi yang baik dan benar sehingga prilaku penjagaan kebersihan gigi dan mulut menjadi lebih baik.…”
Section: Pendahuluanunclassified
“…Pada kondisi fisik tertentu seperti penyandang tunanetra, bentuk media promosi gizi yang digunakan berbeda. Penyandang tunanetra mengalami kondisi umum gangguan atau hambatan dalam indera penglihatannya (10). Indera peraba menjadi indera persepsi utama mereka (11).…”
Section: Pendahuluanunclassified